De portas abertas : a circulação de dádivas e o processo de individualização de universitários/as intercambistas nas moradias da UFMG - Antônio Augusto Oliveira Gonçalves (2017)
In this text, I try to understand the affective-sexual trajectories of students from Latin American countries who come to Belo Horizonte through the exchange programs of the Federal University of Minas Gerais (UFMG). I started with two research questions: how do the social construction of the exchange program and the affective trajectories of the student in the society of origin articulate with the local experiences in Belo Horizonte? What are the affective-sexual experiences that students engage in the course of their stay? Initially through floating observations and interviews, I performed an ethnographic immersion in the UFMG university housing universe (MOP I and II). There were some disciplinary practices in this context, restrictions on visitor entry, panoptic architecture, security inspections, which were superseded by the circulation of gifts, name loans, mattresses and keys, passed on to the exchange students and the residents. This exchange of objects and favors allowed the affective-sexual experiences to be experienced even in front of the disciplinary control in the ordinances of the MOP I and II. Through common coexistence in housing, exchange students and other residents built a web of links and interdependencies, sometimes forging symbolic family relationships between themselves and/or distinguishing themselves in groups. In addition to the relevance of housing in the life of these exchange students in Belo Horizonte, following their affective-sexual trajectories from the societies of origin, it can be verified that they pass through different individualization processes, due to a set of circumstances experienced during exchanges programs: leaving the parents' house, learning a new language, forging new ways of affective-sexual relationships, establishing limits in linking, forming personal tastes, among other things. Through the "mopiana" sociability, the exchange students broke old affection ties, managed in contexts with distinct social grammars, some of them came to reinvent themselves, to construct another conception of itself, in the course of the exchange program.